2018
DOI: 10.1002/jso.25284
|View full text |Cite
|
Sign up to set email alerts
|

Localized synovial sarcoma of the foot or ankle: A series of 32 Cooperative Weichteilsarkom Study Group patients

Abstract: Background: Synovial sarcoma of the foot/ankle is rare. Mutilating surgery is often discussed.Methods: Patients registered from 1981 to 2013 were analyzed. Cooperative Weichteilsarkom Studiengruppe (CWS) protocols recommend chemotherapy for all synovial sarcoma patients.Results: Thirty-two of 330 patients with localized synovial sarcoma had their tumor at the foot/ankle. Eleven of thirty-two tumors were >5 cm. Twenty were T1, 11 T2, and one TX, respectively. Eight (25%) patients underwent primary complete rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The 5-year overall survival rate of soft tissue sarcomas arising in the foot is 76.3 79%, 3,4,17 and the 5-year overall survival rate of synovial sarcomas arising in the foot has been reported to be 86%, with a better prognosis than for synovial sarcomas in the limbs and trunk. 18 Although the 5-year overall survival rate of limb salvage cases in this study showed good prognosis at 94.7%, the 9 cases that underwent belowknee amputation at our hospital (Table 3) showed a significantly poorer prognosis at 55.6% (Fig. 3).…”
Section: Discussionmentioning
confidence: 50%
“…The 5-year overall survival rate of soft tissue sarcomas arising in the foot is 76.3 79%, 3,4,17 and the 5-year overall survival rate of synovial sarcomas arising in the foot has been reported to be 86%, with a better prognosis than for synovial sarcomas in the limbs and trunk. 18 Although the 5-year overall survival rate of limb salvage cases in this study showed good prognosis at 94.7%, the 9 cases that underwent belowknee amputation at our hospital (Table 3) showed a significantly poorer prognosis at 55.6% (Fig. 3).…”
Section: Discussionmentioning
confidence: 50%
“…2,4 We observed a similar 5-year OS rate (88%) for patients presenting with localized disease as described in previously published case series. [7][8][9] For example, Outani et al 7 reported an 80% 5-year OS with 5 hand SS patients. Scully et al 8 reported a 5-year OS of 79% with 14 foot SS patients, and Scheer et al 9 showed the rate to be 86% in 32 foot and ankle SS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The overall 5-year survival rate for all SS is known to be around 50% to 60%, 6 whereas it may be 80% to 86% for hand and foot SS. [7][8][9] The current literature mostly consists of case reports and series with limited cases of either hand or foot SS. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In addition, there is a paucity of literature on hand and foot SS patients presenting with localized disease compared with metastatic disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical information, treatment data, and outcome were available for all. Some had been included in previous analysis (pathological slides were reviewed for the purposes of those studies)(Stegmaier et al 2017 ; Scheer et al 2016a ; Scheer et al 2020 ; Scheer et al 2019 ; Scheer et al 2016b ). The SYT–SSX fusion transcript was routinely analyzed since 2000.…”
Section: Methodsmentioning
confidence: 99%